WOMEN IN MILITARY FAMILIES IN INDONESIA - permana, zein (Salasika, 2024)
ABSTRACT This study explores the roles and experiences of women in military families, focusing on their contributions and challenges in managing family life and military obligations. Women in these families, whether as spouses of military personnel or as military members themselves, face unique pressures that include emotional, psychological, and logistical challenges. The research aims to provide a comprehensive understanding of how these women navigate their responsibilities and the support systems available to them. Using a scoping review methodology, relevant literature was synthesized to identify key themes, including emotional support, mental health, role balancing, and community involvement. The findings reveal that women in military families often shoulder significant burdens, yet their contributions are essential to family stability and the success of military operations. The study concludes that stronger mental health services and gender-sensitive policies within military institutions are needed to better support these women. The research also highlights the importance of community and policy interventions to enhance the well-being and sustainability of military families, especially in non-Western contexts where cultural factors may add additional layers of complexity. These insights can inform future policies aimed at improving the welfare of military families and their communities.